Hygrothermal effect on hybrid composite by using filement winding process - Osman, Edynoor (2014)
Nowadays, filament winding process has evolved in manufacturing of polymer composites industries. In addition, filament winding process of polymer matrix composite offered the most cost effective method, good part definition and correctly fibre placement that will give very high strength to weight ratio. In this project, a hygrothermal effect on GlassCarbon/Epoxy hybrid composite were studied and revealed. The non geodesic pattern of filament winding was used with the winding speed of 15.24 -30.48 linear metre/min. Fibre tensioning weight of l kg and winding angles of 30° is created in order to produce the wound samples of hybrid composite. The hybrid composite was wound by using the orientation of± 30°with the total number of six (6) layers. While for hygrothermal effect has been carried out in humidity chamber for 3 days (72hrs). The controls temperatures of 60°C and 80°C has been set up as well as percentage of humidity 50%, 70% and 90% are used. From the testing result, hybridization of glass and carbon fibre shows the highest in tensile and flexure test which represent 90.27 MPa and 198.10 MPa respectively as compared to non-hybrid samples. Moisture absorption test shows most of the hybrid samples are gradually increased over heat and humidity. As a result, Glass-Carbon 80°C/90% shows the highest value of moisture absorbed, 0.77%. Meanwhile, the involvement of highest heat and humidity shows the decreased in value of tensile and flexure strength, 75.80 MPa and 157. 15 MPa respectively. As thermal analysis results, shows the reduction of T g with the increase of heat and humidity that indicate the effect of the hygrothermal. From fractography analysis by using Stereo Microscope Stemi 2000-C, Glass-Carbon/Epoxy 80°C/90% has shown catastrophic damage, big crack and longest delamination of fibre pull out, 10.39 mm. The criterion of fracture revealed that the involvement of heat and humidity give a big impact towards the mechanical and physical properties of hybrid composite material.